Notes on the taxonomic position of several species of the genus Diphascon (Tardigrada, Hypsibiidae) - Tumanov, Denis V. (Zootaxa, 2018)
For this paper I analysed the descriptions of all species, attributed to the genus Diphascon Plate, 1889, to ascertain if they fit the diagnosis of this genus, provided by Bertolani et al. 2014. Thirty four species (the majority of the species diversity classified within the genus) fully match its emended diagnosis, while three: Diphascon opisthoglyptum Maucci, 1987, Diphascon procerum Pilato, Sabella & Lisi, 2014 and Diphascon ziliense Lisi, Sabella & Pilato, 2014, demonstrate a combination of characters, typical to the genus Pilatobius Bertolani et al., 2014. I propose the transfer these three species to the genus Pilatobius, thus their new taxonomic positions are as follows: Pilatobius opisthoglyptus (Maucci, 1987) comb. nov., Pilatobius procerus (Pilato, Sabella & Lisi, 2014) comb. nov. and Pilatobius ziliense (Lisi, Sabella & Pilato, 2014) comb. nov. Descriptions of three other Diphascon species (Diphascon mariae (Mihelčič, 1951), Diphascon rivulare (Mihelčič, 1967) and Diphascon punctatum (Iharos, 1962)) contain too little detail to conclude on their taxonomic position. The species Pilatobius halapiense (Iharos, 1964) was erroneously transferred from the genus Diphascon, and here I suggest it is transferred back to Diphascon. The new taxonomic position of this species is: Diphascon halapiense (Iharos, 1964) comb. nov. Emended list of species, attributed to the genus Diphascon is given.